Attachment, Depression, Anxiety, Stress, Coping and Alexithymia in Sexually Abused Adolescents - Demirtaş, Sibel; Cömert, Itır Tarı (Elsevier, 2017)
Child sexual abuse is the most hidden phenomenon among child abuse types with psychological, medical, judicial and educational and sociological aspects. Its’ adverse effects will be done in order to explain the relationship between attachment styles, depression, anxiety, stress levels and coping styles and alexithymic characteristics of sexual abuse adolescents. Risk and protective factors need to be identified and supported with methods that will contribute to overcome psychological problems for the sake of children and adolescents exposed to severe traumatic effects of sexual abuse. It is necessary to apply the effective practices and models to the adolescents experienced sexual abuse for healthy and safe lifestyles while taking that today’s victims may be the agents of tomorrow into consideration Sexual abuse should be integrated with its direct/indirect effects in short and long term and protective measures should be improved as well as preventive measures.